Analysis of microbial diversity in the feces of Arborophila rufipectus - Ma, Xiaoping; Li, Junshu; Chen, Benping; Li, Xinni; Ling, Zhenwen; Feng, Shenglin; Cao, Sanjie; Zuo, Zhicai; Deng, Junliang; Huang, Xiaobo; Cai, Dongjie; Wen, Yiping; et al. (Frontiers in Microbiology, 2023)
Intestinal microbiota composition plays a crucial role in modulating the health of the host. This evaluation indicator is very sensitive and profoundly impacts the protection of endangered species. Currently, information on the gut microbiota of wild birds remains scarce. Therefore, this study aimed to describe the gut microbial community structure and potentially, the pathogen composition of wild Arborophila rufipectus. To guarantee comprehensive data analysis, we collected fecal samples from wild A. rufipectus and Lophura nycthemera in their habitats for two quarters. The 16S rRNA gene was then sequenced using high-throughput sequencing technology to examine the intestinal core microbiota, microbial diversity, and potential pathogens with the aim of determining if the composition of the intestinal microflora varies seasonally. The gut microbiota of A. rufipectus and L. nycthemera primarily comprised four phyla: Proteobacteria (45.98%), Firmicutes (35.65%), Bacteroidetes (11.77%), and Actinobacteria (3.48%), which accounted for 96.88% of the total microbial composition in all samples. At the genus level, core microorganisms were found, including Shigella (10.38%), Clostridium (6.16%), Pseudomonas (3.03%), and Rickettsiella (1.99%). In these genera, certain microbial species have been shown to be pathogenic. This study provides important indicators for analyzing the health status of A. rufipectus and formulating protective measures.